2016
DOI: 10.1007/s10964-016-0494-2
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Internet Use: Two Longitudinal Studies of Excessive Internet Use, Depressive Symptoms, School Burnout and Engagement Among Finnish Early and Late Adolescents

Abstract: Recent research shows an increased concern with well-being at school and potential problems associated with students' use of socio-digital technologies, i.e., the mobile devices, computers, social media, and the Internet. Simultaneously with supporting creative social activities, socio-digital participation may also lead to compulsive and addictive behavioral patterns affecting both general and school-related mental health problems. Using two longitudinal data waves gathered among 1702 (53 % female) early (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 46 publications
14
170
0
7
Order By: Relevance
“…Thus, if appropriately used, interned media can be helpful for sustaining attention, memory and social communication skills. However, when excessively used, they may interfere with school work and sleep time and, if chronically continued, may result in an imbalance of circadian rhythms [23]. Furthermore, internet users are continuously exposed to new messages or data, and this constant exposure can interrupt their concentration on schoolwork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if appropriately used, interned media can be helpful for sustaining attention, memory and social communication skills. However, when excessively used, they may interfere with school work and sleep time and, if chronically continued, may result in an imbalance of circadian rhythms [23]. Furthermore, internet users are continuously exposed to new messages or data, and this constant exposure can interrupt their concentration on schoolwork.…”
Section: Discussionmentioning
confidence: 99%
“…Problematic internet use has been suggested to be related to lower school grades [22]. In an earlier prospective study, internet overuse and school burnout were shown to reciprocally affect each other [23]. In addition to the distraction from schoolwork and the relative shortage of time for academic activities caused by internet overuse, socioeconomic factors such as income, parental education level, and region of residence; psychological factors including stress; and physical factors such as medication use, smoking and alcohol use may mediate the effects of internet use on school performance.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has been partly explained by self-applied pressure to be perfect in all aspects of life, including school, the social sphere, and physical appearance. This pressure has increased with the introduction of social media in daily life, such as Facebook, Snapchat, and Instagram, according to a Finnish study [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Excessive ICT use. Compulsive and harmful digital technology use was assessed with a 5-item scale earlier employed by Salmela-Aro, Upadyaya, Hakkarainen, Lonka, and Alho (2017). A sample item reads, "Using ICT causes me to neglect my schoolwork".…”
Section: Methodsmentioning
confidence: 99%